Assessing the indicated impact of cantrang (boat Danish seine) based on catch characteristics in Java Sea, Indonesia - Am Azbas Taurusman; Tri Laela Wulandari; Tri Wiji Nurani; Budy Wiryawan; Irfan Yulianto; Yopi Novita; Ronny Irawan Wahju (Fisheries and Aquatic Sciences)
Cantrang (boat Danish seine) has been illegal since 2015 but remains prevalent in Indonesia’s Java Sea. Despite known negative impacts, no comprehensive ecological assessment of cantrang fishing exists. This study evaluates its effects by analyzing catch data based on taxa, trophic level, habitat, and fishing vulnerability by a multivariate approach. In this study, the size of 60 cantrang vessel samples were grouped into 4, namely 20–30, 31–50, 51–100, and 101–200 gross tons (GT), representing the spatial distribution of the fishing grounds. Larger vessels catch more diverse and abundant fish, primarily reef-associated and demersal species groups. There was a significant difference in the fishing vessel’s size on the catch’s composition (analysis of similarities, ANOSIM R = 0.114, p = 0.024). The dominant catches were families of Loliginidae (Loligo sp., 24.38%) and Nemipteridae (Nemipterus nematophorus, 19.29%), trophic level 2.7 (34.41–43.18%), reef-associated and demersal fish (37.06–46.09%), and low vulnerability group of fish (58.01–64.56%). Additionally, 2.69–8.56% of the endangered, threatened, and protected species of wedgefish (Rhyncobatus sp.) were also caught by the cantrang. This study confirms the impacts of cantrang on fish resources in the Java Sea, Indonesia’s Fisheries Management Area 712. The findings emphasize the need to improve management strategies to achieve sustainable fish resources and marine biodiversity in the region.